Pencegahan Stunting Melalui Pelatihan Senam Bayi (Baby Gym) di Wilayah Kerja Puskesmas Tipo: Prevention of Stunting Through Baby Gym Training in the Working Area of ​​the Tipo Health Center - Hastuti Usman; Sarliana Sarliana; Asri Widyayanti (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The quality of children is determined by the continuity of the process of growth and development. One of the growth and development disorders is stunting which is caused by lack of nutritional intake for a long time, if monitoring and detection is not carried out early, it will have an impact on the physical and cognitive development of children in the future. The incidence of stunting in Donggala Regency was 29.5% and the Tipo Health Center contributed 44.4%. Interventions carried out in preventing stunting are varied, baby gymnastics can be an alternative to help stimulate the hypothalamic hunger center so as to trigger the desire of infants to breastfeed/eat. Baby gymnastics requires skill and knowledge. Analysis of the situation at the Tipo Health Center, the knowledge of the community, especially mothers, is still low, lack of skills and limited facilities and infrastructure. This activity aims to increase the knowledge and skills of mothers in infant gymnastics. This activity was carried out at the Tipo Health Center, with 20 respondents. The method used is lecture and discussion. Evaluation is done in the form of a pre-post test. The mean result of the pre-test score was 64.20 and an increase in the post-test score was 91.56, an increase in the score was 27.36. Giving baby gymnastics is very important to support the growth and development of babies which can prevent stunting ABSTRAK Kualitas anak ditentukan oleh keberlangsungan proses tumbuh-kembangnya. Salah satu gangguan tumbuh-kembang adalah stunting yang disebabkan kurangnya asupan gizi dalam waktu yang cukup lama, apabila tidak dilakukan pemantauan dan deteksi secara dini, akan berdampak pada perkembangan fisik dan kognitif anak di masa depan. Kejadian stunting Kabupaten Donggala 29,5% dan Puskesmas Tipo menyumbang sebesar 44,4%. Intervensi yang dilakukan dalam pencegahan stunting beragam, senam bayi dapat menjadi salah satu alternatif untuk membantu merangsang pusat lapar hipotalamus sehingga memicu keinginan bayi balita untuk menyusui/makan. Senam bayi memerlukan keterampilan dan pengetahuan. Analisis situasi di Puskesmas Tipo pengetahuan masyarakat terutama ibu masih rendah, kurangnya keterampilan dan terbatasnya sarana dan prasarana. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan keterampilan ibu dalam senam bayi. Kegiatan ini dilaksanakan di Puskesmas Tipo, dengan 20 responden. Metode yang digunakan ceramah dan diskusi. Evaluasi dilakukan dalam bentuk pre-post test. Hasil rerata skor pre-test 64,20 dan terjadi peningkatan skor post-test 91,56, terjadi peningkatan skor sebanyak 27,36. Pemberian senam bayi sangat penting untuk mendukung tumbuh kembang bayi yang dapat mencegah terjadinya stunting.